Culinary Financial Control System Implementation of Microsoft Access-Based Information System as an Effort to Assist Financial Management Restaurant - Achmad, Fauzi Fahmi; Andriyansyah, Muhammad; Putra, Alif Naufal; Santosa, Alam (Universitas Komputer Indonesia, 2025)
This study aimed to resolve financial management challenges at Haji Iros Restaurant, which stemmed from an inefficient manual bookkeeping system causing discrepancies between predicted and actual income. The research goal was to design and implement an integrated financial management system using Microsoft Access to automate transactions, sales recording, and report generation. The methodology involved conducting surveys and interviews to identify specific problems, followed by the systematic design and development of a relational database system. Key components included tables for menu and transaction data, input forms, processing queries, and automated financial reports. The result demonstrated that the implemented system successfully reduced bookkeeping time and minimized calculation errors. The discussion highlights how the system’s integration ensures data consistency and provides real-time financial transparency. In conclusion, the Microsoft Access-based system effectively improves the accuracy and efficiency of financial management for the restaurant. The impact of this research is significant support of MS’E's digital transformation, leading to strengthened operational efficiency, enhanced financial control, and greater potential for economic growth, aligning with the national theme of strengthening small businesses.